Foreign aid and climate change policy: What can('t) the data tell us? - Daniel Y. Kono; Gabriella R. Montinola (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Climate-related foreign aid is on the rise, with signatories to the Paris Climate agreement pledging US100 billion annually to promote mitigation and adaptation in recipient countries. While this seems like a welcome development, we have little evidence that climate aid actually encourages recipients to adopt climate legislation. In this paper, we examine the relationship between climate aid and recipient climate policy. Using multiple measures of each, we find no evidence that the former is systematically related to the latter. Although this suggests that climate aid is ineffective, this conclusion must be qualified due to the poor quality of both climate aid and climate policy data. More definitive conclusions will require more accurate coding of climate aid as well as better climate policy measures that distinguish truly consequential policies from less consequential ones.
Keywords: C19; F35; F59; Q58; 330; adaptation; climate change; mitigation; environmental policy; official development assistance